2016
DOI: 10.1080/09168451.2015.1072460
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of betulin from Betula platyphylla bark on scopolamine-induced amnesic mice

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease induced by cholinergic neuron damage or amyloid-beta aggregation in the basal forebrain region and resulting in cognitive disorder. We previously reported on the neuroprotective effects of Betula platyphylla bark (BPB) in an amyloid-beta-induced amnesic mouse model. In this study, we obtained a cognitive-enhancing compound by assessing results using a scopolamine-induced amnesic mouse model. Our results show that oral treatment of mice with BPB and betuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Pharmacokinetic research in rats has showed that daily intraperitoneal administration of 60 mg/kg of betulin for 28 days does not result in toxicity [37]. Oral administration of 5 and 10 mg/kg betulin improved the scopolamine-induced amnesia in mouse models, and intraperitoneal administration of betulin (10 and 20 mg/kg) improved autoimmune hepatitis in mice [11,38]. Additionally, betulin administration (10 mg/kg) significantly decreased lung metastasis of CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic research in rats has showed that daily intraperitoneal administration of 60 mg/kg of betulin for 28 days does not result in toxicity [37]. Oral administration of 5 and 10 mg/kg betulin improved the scopolamine-induced amnesia in mouse models, and intraperitoneal administration of betulin (10 and 20 mg/kg) improved autoimmune hepatitis in mice [11,38]. Additionally, betulin administration (10 mg/kg) significantly decreased lung metastasis of CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Betulin and its derivatives have been widely used in traditional herbal medicine against various inflammatory diseases and ischemia. 14,15 Betulin is cytoprotective, and its anti-inflammatory actions are based on radical quenching and antioxidative effects. 14,15 Thus, betulin could serve as a potential therapeutic candidate for brain disorders.…”
mentioning
confidence: 99%
“…14,15 Betulin is cytoprotective, and its anti-inflammatory actions are based on radical quenching and antioxidative effects. 14,15 Thus, betulin could serve as a potential therapeutic candidate for brain disorders. However, no study has yet reported the biological mechanism of betulin in ER stress-injured HT-22 in vitro models.…”
mentioning
confidence: 99%
“…Investigations into specific activity of these molecules on Alzheimer's disease models were conducted in order to assess disease-specific potential of compounds [1,8,23]. Nobiletin from citrus was tested at a 30mg/kg dose over three months in a triple transgenic mouse model and was found to reverse the short-term memory and recognition task performance by reducing reactive oxygen species in the hippocampus [1].…”
Section: Alzheimer'smentioning
confidence: 99%